2012
DOI: 10.1002/pds.3389
|View full text |Cite
|
Sign up to set email alerts
|

Different indications, warnings and precautions, and contraindications for the same drug—an international comparison of prescribing information for commonly used psychiatric drugs

Abstract: This substantial variation in key prescribing information across countries highlights the need for a better international cooperation and standardization of prescribing information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 11 publications
0
18
0
1
Order By: Relevance
“…Bei Präparaten anderer Hersteller findet sich exakt der gleiche Hinweis, jedoch im Abschnitt 4.4. Ähnliche Inkonsistenz bei GEG∪WARN bezüglich Wechselwirkungen in verschiedenen Fachinformationen sind bereits bekannt und deutsche und europäische Behörden sollten eine bessere Harmonisierung anstreben [17].…”
Section: Qualität Der Pädiatrischen Informationenunclassified
“…Bei Präparaten anderer Hersteller findet sich exakt der gleiche Hinweis, jedoch im Abschnitt 4.4. Ähnliche Inkonsistenz bei GEG∪WARN bezüglich Wechselwirkungen in verschiedenen Fachinformationen sind bereits bekannt und deutsche und europäische Behörden sollten eine bessere Harmonisierung anstreben [17].…”
Section: Qualität Der Pädiatrischen Informationenunclassified
“…However, when we assessed adverse drug events in an emergency department, we observed that disagreement between raters whether or not an ignored contraindication contributed to an adverse drug event was frequently attributable to the fact that the two raters had consulted SPCs from different manufacturers for the same generic drug 2 . In conjunction with publications on individual aspects of SPCs, this increased our concern that the information provided in SPCs in general may not be as up to date, reliable, and clinically useful as one would expect from officially approved documents 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 . This prompted us to systematically investigate the consistency, comprehensiveness, and clinical applicability of critical information provided in SPCs for three major drug markets (the United States, the United Kingdom, and Germany).…”
mentioning
confidence: 99%
“…The label is intended to assist healthcare professionals in choosing the most appropriate therapy under their circumstances . However, the safety and efficacy information provided in the label may depend on the country in which a drug is marketed due to different requirements from regulatory authorities in each country as well as in their approaches to pediatric risk‐benefit analysis . In addition, it could be a market‐driven decision by the company to improve labeling information for drugs used in children based on data from clinical trials conducted in domestic or foreign pediatric patients .…”
Section: Discussionmentioning
confidence: 99%
“…26 However, the safety and efficacy information provided in the label may depend on the country in which a drug is marketed due to different requirements from regulatory authorities in each country as well as in their approaches to pediatric risk-benefit analysis. 27,28 In addition, it could be a market-driven decision by the company to improve labeling information for drugs used in children based on data from clinical trials conducted in domestic or foreign pediatric patients. 7 This study indicated that there were limited pediatric indications and narrowly defined age groups based on Korean drug labels compared with pediatric information provided in drug labels approved by the FDA.…”
Section: Discussionmentioning
confidence: 99%